A new model for evaluation of cavity shape and volume during Underground Coal Gasification process - Jowkar, Amin; Sereshki, Farhang; Najafi, Mehdi (Energy (Oxford), 2018)
Coal seams are converted to syngas by advanced thermo-chemical processes through Underground Coal Gasification (UCG) method. Inability to predict the shape and volume of the underground cavity is an important scientific gap in UCG method which is the main subject of this paper. For this purpose, firstly, a series of equations are introduced to predict the cavity growth dimensions over time. Subsequently, these equations are extended in numerical simulation of the Computational Fluid Dynamics (CFD), incorporating the commercial COMSOL software. According to the simulation, the amount of oxidant necessary to convert a certain amount of coal (in the heterogeneous phase) is calculated. The model results indicated that the shape and volume of cavity could be predicted at the onset of the gasification process. The numerical results agreed well with the field data. •A new method for predicting cavity shape and volume has been presented.•The amount of coal burning in each UCG-panel is controlled.•Model predictions are in agreement with the results of UCG field data.•Primary and basic foundations for commercializing the UCG method has been presented by a new design.